Flavonoid Detection in Hydroethanolic Extract of Pouteria torta (Sapotaceae) Leaves by HPLC-DAD and the Determination of Its Mutagenic Activity - Costa, Daryne L. M. G. [UNESP]; Rinaldo, Daniel [UNESP]; Varanda, Eliana A. [UNESP]; Sousa, Juliana F. de [UNESP]; Nasser, Ana L. M. [UNESP]; Silva, Ana C. Z. [UNESP]; Baldoqui, Debora C.; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP] (Mary Ann Liebert, Inc, 2014)
It is well known that phytotherapy has grown in popularity in recent years. Because a drug cannot be administered without ensuring its effectiveness and safety, the standardization and regulation of phytotherapeutic drugs are required by the global market and governmental authorities. This article describes a simple and reliable high-performance liquid chromatography-diode array detection analysis method for the simultaneous detection of myricetin-3-O-beta-D-galactopyranoside, myricetin-3-O-alpha-L-arabinopyranoside, and myricetin-3-O-alpha-L-rhaminopyranoside present in the hydroethanolic extract (ethanol/H2O, 7:3, v/v) of Pouteria torta. The mutagenic activity of the extract was evaluated on Salmonella typhimurium and by an in vivo micronucleus test on the peripheral blood cells of Swiss mice. The linearity, sensitivity, selectivity, repeatability, accuracy, and precision of the assay were evaluated. The analytical curves were linear and exhibited good repeatability (with a deviation of less than 5%) and demonstrated good recovery (within the 83-107% range). The results demonstrate that the hydroethanolic extract exhibited a mutagenic activity in both assays, suggesting caution in the use of this plant in folk medicine.
Keywords: mutagenicity; liquid chromatography; Pouteria torta; flavonoids; quantification